Biocatalysis mechanisms and characterization of a novel denitrification process with porphyrin compounds based on the electron transfer chain. (October 2018) - Xie, Zhen; Guo, Jianbo; Lu, Caicai; Song, Yuanyuan; Xing, Yajuan; Yang, Qingxiong; Han, Yi; Li, Haibo
Graphical abstract: Highlights: First report of exogenous hemin effectively enhanced the denitrification process. The activation energy of hemin-supplemented system decreased 87% compared to control. Both the Fe 3+ atom and the porphyrin ligand might be the catalytic sites of hemin. The mechanism of hemin participated the denitrification ETC was explored. Abstract: In this research, the nitrate reduction rate increased 2–3 fold in the presence of five different porphyrin compounds (0.25 mM), among which hemin expressed the best accelerating effectiveness. Therefore, hemin was used to explore the catalytic characteristics and mechanisms during denitrification. The relationship between hemin concentrations (Chemin ) and nitrate reduction rates ( k ) could be best described by the equation k = 8.7463 + 0.44528ln (Chemin -0.00993) (R 2 = 0.9908). Furthermore, the activation energy decreased 87% compared to the hemin-free system. Two active centers of hemin, the Fe 3+ atom and the porphyrin ligand, might be involved in catalyzing the denitrification process. Additionally, the accelerating site of hemin in the denitrification electron transfer chain was elucidated by different metabolic inhibitors. This study provides a better understanding of porphyrin compounds in bio-multistage redox reactions and is a promising strategy for its practice application.